THE EFFECTS OF ISLAMIC BRANDING AND CUSTOMER RELATIONSHIP MARKETING ON CUSTOMER LOYALTY THROUGH SATISFACTION AS THE MEDIATING VARIABLE - Adha, Mufti Alam; Silmi, Afrida Fadkhi; Nahar, Faiza Husnayeni (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research aims: This study aims to analyze the effects of Islamic Branding and Customer Relationship Marketing (CRM) on Customer Loyalty, with Customer Satisfaction as a mediating variable. The research focuses on understanding how Islamic values embedded in branding and relationship strategies influence Muslim consumer loyalty. Design/Methodology/Approach: A quantitative approach was employed using a structured questionnaire distributed to 120 Muslim consumers in West Sumatra. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test both direct and indirect relationships among the variables. Research findings: The findings indicate that both Islamic Branding and CRM have significant positive effects on Customer Satisfaction and Customer Loyalty. Furthermore, Customer Satisfaction partially mediates the relationship between Islamic Branding and Loyalty, as well as between CRM and Loyalty. This confirms that customer satisfaction strengthens the effect of Islamic branding and CRM on loyalty. Theoretical Contribution/Originality: This study contributes to the field of Islamic marketing by integrating Islamic Branding and CRM into a comprehensive loyalty model. It highlights the importance of religious and relational values in shaping customer satisfaction and loyalty within Islamic consumer behavior. Practitioners/Policy Implications: For marketers and policy makers, the results suggest that applying Islamic principles in branding and building strong, trust-based relationships with consumers can significantly enhance satisfaction and loyalty. This is particularly relevant for businesses targeting Muslim markets such as halal products, Islamic banking, and sharia-compliant services. Research Limitations/Implications: The study is limited to a specific region and sample size, which may limit generalizability. Future studies should include larger and more diverse populations, as well as consider longitudinal data to further validate the findings across different cultural and market contexts